1997
DOI: 10.1590/s0102-311x1997000500009
|View full text |Cite
|
Sign up to set email alerts
|

Stomach cancer incidence in Brazil: an ecologic study with selected risk factors

Abstract: Contrary to many industrialized countries in which a sharp decline in stomach cancer incidence has been observed, Brazil still shows intermediate to high incidence rates. An ecologic analysis was performed to explore variables possibly associated with the development of stomach cancer. Cluster analysis, principal component analysis, and factor analysis were carried out with population data, including the following: stomach cancer incidence rates in the early 1990s obtained from population-based cancer registri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2003
2003
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 13 publications
0
8
0
1
Order By: Relevance
“…Similar results have been reported in other studies conducted in Brazil (16,30) . This finding might be explained by the etiopathogenesis of gastric adenocarcinoma of the intestinal type, which is characterized by atrophic gastritis and intestinal metaplasia and involves factors such as dietary habits, exposure to H. pylori and smoking that share the preference for distal portions of the stomach (5,13,14,19,36) . Other studies have demonstrated the participation of these factors in the etiopathogenesis of gastric adenocarcinoma in the State of Pará (9,25,27,28,37) .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similar results have been reported in other studies conducted in Brazil (16,30) . This finding might be explained by the etiopathogenesis of gastric adenocarcinoma of the intestinal type, which is characterized by atrophic gastritis and intestinal metaplasia and involves factors such as dietary habits, exposure to H. pylori and smoking that share the preference for distal portions of the stomach (5,13,14,19,36) . Other studies have demonstrated the participation of these factors in the etiopathogenesis of gastric adenocarcinoma in the State of Pará (9,25,27,28,37) .…”
Section: Discussionmentioning
confidence: 99%
“…The macroscopic features of the tumor were evaluated according to the Borrmann classification and the classification of the Japanese Society for Gastroenterological Endoscopy (JSGE) (20) . The histological type of the tumor was evaluated according to the Lauren classification (14) . The final stage of the tumor was established based on the American Joint Committee on Cancer (UICC/AJCC) TNM Staging System (2002) (10) .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Various risk factors have been recognized such as helicobacter pylori (H pylori) infection, cured meat, smoking, and alcohol while Mediterranean diet, vegetables and fruits, vitamin C, retinol and high intake of cereal fiber decrease the risk of stomach cancer (Kolonel et al, 1981;Demirer et al, 1990;Schottenfeld and Fraumeni, 2006;Wang, 2009;Gonzalez and Riboli, 2010). An ecologic analysis in Brazil suggested that differences in living standards among populations probably have an important role in incidence differences (Koifman and Koifman, 1997). The high level of education in men and higher SEP were associated with lower stomach cancer risk and for education exist even after age adjustment (RR highest to lowest level=0.54) which was diluted by variables such as smoking, intake of vitamin C, beta carotene, alcohol, coffee and family history of stomach cancer van Loon et al, 1998).…”
Section: 1669 Correlation Of Cancer Incidence With Probable Risk Facmentioning
confidence: 99%
“…O câncer do estômago é o segundo mais freqüente no Estado de São Paulo (27,28) e a maior causa de morte por neoplasias no Brasil (28,38) . O adenocarcinoma é o tipo histológico mais freqüente, ocorrendo em 90% a 95% dos pacientes (7,50) .…”
Section: Introductionunclassified